Robots, Labor Markets, and Family Behavior - Massimo Anelli; Osea Giuntella; Luca Stella (Institute of Labor Economics (IZA), 2019)
Robots have radically changed the demand for skills and the role of workers in production at an unprecedented pace, with little scope for human capital adjustments. This has affected the job stability and the economic perspectives of large parts of the population in all industrialized countries. Recent evidence on the US labor market has shown negative effects of robots on employment and wages. In this study, we examine how exposure to robots and its consequences on job stability and economic uncertainty have affected individual demographic behavior. To establish this relationship, we use data from the American Community Survey and the International Federation of Robotics and we adopt an empirical strategy that relies on regional industry specialization before the advent of robots combined with the growth of robot adoption by industry. We first document the differential effect of robots on the labor market opportunities of men and women. We find that in regions that were more exposed to robots, the gender-income and labor-force-participation gaps declined. We then show that US regions affected by intense robot penetration experienced a decrease in new marriages, and an increase in both divorce and cohabitation. While there was no change in overall fertility rate, marital fertility declined, and there was an increase in out-of-wedlock births. Our findings are consistent with the hypothesis that the changes in labor markets triggered by robot adoption increased uncertainty, reduced the relative marriage-market value of men, and the willingness to commit for the long term.
Keywords: J12; J13; J21; J23; J24; 330; automation; marriage market; divorce; fertility; cohabitation; gender